2015
DOI: 10.1007/s10896-015-9740-8
|View full text |Cite
|
Sign up to set email alerts
|

Stress Management and Intimate Partner Violence: A Randomized Controlled Trial

Abstract: Intimate partner violence is a major health problem for women; some of the most common symptoms of violence are depression, psychological distress, and sleep disturbances. In this parallel randomized controlled trial, which took place in Athens-Greece, abused women were randomly assigned to undergo either an 8-week stress management program (n=16; relaxation breathing and progressive muscle relaxation, twice a day counseling) or standard shelter services (n=18). Selfreported validated measures were used to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…The majority of studies were conducted within the United States ( n = 39) and the international studies varied widely with samples from Canada, China, Greece, Peru, South Africa, Israel, Spain, Sweden, and Korea (Crespo & Arinero, 2010; Cripe et al, 2010; Grip et al, 2011; S. Kim & Kim, 2001; Kokka et al, 2016; Michalopoulou, Tzamalouka, Chrousos, & Darviri, 2015; Miller, Howell, & Graham-Bermann, 2014; Peled et al, 2010; Pronyk et al, 2006; Tiwari et al, 2005, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies were conducted within the United States ( n = 39) and the international studies varied widely with samples from Canada, China, Greece, Peru, South Africa, Israel, Spain, Sweden, and Korea (Crespo & Arinero, 2010; Cripe et al, 2010; Grip et al, 2011; S. Kim & Kim, 2001; Kokka et al, 2016; Michalopoulou, Tzamalouka, Chrousos, & Darviri, 2015; Miller, Howell, & Graham-Bermann, 2014; Peled et al, 2010; Pronyk et al, 2006; Tiwari et al, 2005, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…M. Sullivan et al, 1992, 1999, 2002; Tan et al, 1995; Tiwari et al, 2005, 2010), while the rest were clinically focused ( n = 19). Ten of the 19 clinically focused interventions were delivered individually (Franzblau et al, 2008; Iverson et al, 2009; Johnson & Zlotnick, 2006; Johnson et al, 2011; Kubany et al, 2003, 2004; Michalopoulou et al, 2015; Reed & Enright, 2006; Saftlas et al, 2014; Zlotnick et al, 2011), 7 were delivered in a group format (Cort et al, 2014; Crespo & Arinero, 2010; Iverson et al, 2011; Kaslow et al, 2010; S. Kim & Kim, 2001; Kokka et al, 2016; M.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of strategies to address IPV, the randomized controlled trial of Michalopoulou, Tzamalouka, Chrouros and Darviri (2015) in Greece evaluated the impact of interventions to reduce the psychological impacts of IPV such as stress, depression, locus of control and coping. Their study showed a moderate effect of a stress management program on stress (but none of the other outcomes).…”
Section: Resultsmentioning
confidence: 99%
“…Michalopoulou E, Tzamalouka G, Chrousos GP, Darviri C (2015) (27) Journal of Family Violence (CINAHL) 34 women/Randomized controlled trial/(Greece) Stress, depression, anxiety and self esteem 2B…”
Section: Level Of Evidencementioning
confidence: 99%
“…A randomized controlled trial developed with Greek IPV women victims who suffered some non-psychotic mental disorder observed that the perceived stress in the intervention group was significantly decreased after 8 weeks of relaxation (exercises), however no significant outcome was observed for hours of sleep and depression (27) . There is also evidence that empowering women abused by their partners can be a protective factor against negative results to their mental health (16) .…”
Section: Ptsd and Depression 2c …Continuationmentioning
confidence: 99%